(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Nature and the constructed environment present various topics and settings for artistic expression and these have been the worry of artists all through the ages, particularly painters. This concentrate along these lines analyzes the implantation of landscape painting as an artistic classification and a visual archive of financial and urban improvement in India. The landscape painting is exceptionally intriguing in spite of the fact that it has no deliberate history. There are divider paintings in Egyptian tombs and in Rome, which can be classified as landscape paintings since they speak to rocks, plants and trees in their natural form. We may say that landscape Painting in Europe was an impossible to miss invention of the renaissance. The landscape components were bit by bit permitted to predominant this episode displayed in a painting. Indian landscape takes birth in a playground of emotions in pain, preference, craving and trust, in the delights of straightforward living and the constancy and energy of lives is rhythm tempered by scholarly reverberations of an once brilliant human progress. Landscape painting holds in contemporary Indian Art. In fact, after landscape painters are celebrated in India in particular - Akbar Padamasee, Paramjit Singh, Ganesh Haloi, Ram Kumar, Satish Chandra, Paresh Marty, Sanjay Bhattacharya, Rajnish Kaur, Dr. Ram Kanwar, Prof. Ashfaq Rizvi. In the field of modern landscape, I would like to select four artists i.e. Ram Kumar, Parmjeet Singh, Satish Chandra and Dr. Ram Kanwar, who are extraordinary painters of all over India and known for their work in India, as well as in the entire world.